Uji Efek Sitotoksik Ekstrak Etanol Kulit Buah Asam Kandis (Garcinia cowa Roxb.) Terhadap Sel Kanker Payudara T47d dengan Metoda Mtt (Microtetrazolium) Assay - Wahyuni, Fatma Sri; Sutma, Suci; Aldi, Yufri (Jurnal Sains dan Teknologi Farmasi, 2011)
The evaluation of cytotoxic effect on ethanolic extract from the fruit rinds of asam kandis (Garcinia cowa Roxb.) on T47D human breast cancer cells in vitro had been evaluated. The cytotoxic effect was carried out by using MTT assay. Extraction of dried fruit rinds of G. cowa Roxb. was macerated with ethanol 70%. The extract was prepared into 4 concentration groups, 100, 10, 1, and 0,1 Î¼g/ml. Results showed that the IC50 of G. cowa Roxb. ethanolic extract was 19,33 Î¼g/ml Â± 1,15 on breast cancer T47D cells. The percentage of cells viability and concentration were analyzed analyzed by the two-way analysis of variance (ANOVA) followed by Duncan test. Result showed that the ethanolic extract of G. cowa Roxb gave a significant effect on T47D breast cancer cells viability (P<0.05).